Influence of intrinsic strain on irradiation induced damage: the role of threshold displacement and surface binding energies. (5th December 2016) - Guénolé, J.; Prakash, A.; Bitzek, E.
Abstract: Focused ion beam (FIB) machining has become a standard tool for sample preparation and in combination with digital image correlation (DIC) for the evaluation of local intrinsic stresses by measuring strain relaxation. However, FIB milling always leads to irradiation damage of the material. Current models for the formation of irradiation damage and the sputter yield are based on two key parameters, the threshold displacement energy (TDE) and surface binding energy (SBE), which are usually determined from unstrained systems with idealized surfaces. Here we use atomistic simulations to determine the TDE and SBE for strained silicon and aluminum and compare the results to full cascade simulations. A clear, material class dependent influence of the strain state on the TDE is observed, and surface amorphisation is shown to significantly increase the SBE of 001 surfaces. Highlights: The threshold displacement energy is shown to be strain dependent. The strain dependence is related to the anarmonicity of the potential. Cascade simulations show strain dependant damage formation and sputter rate. Surface binding energy with realistic surface show significant increase compare to the typical idealized situation. Graphical Abstract: